2013
DOI: 10.1038/onc.2013.492
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and cancer stem cells: the sword and the shield

Abstract: Emerging chemotherapy drugs and targeted therapies have been widely applied in anticancer treatment and have given oncologists a promising future. Nevertheless, regeneration and recurrence are still huge obstacles on the way to cure cancer. Cancer stem cells (CSCs) are capable of self-renewal, tumor initiation, recurrence, metastasis, therapy resistance, and reside as a subset in many, if not all, cancers. Therefore, therapeutics specifically targeting and killing CSCs are being identified, and may be promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 107 publications
(139 reference statements)
1
119
0
Order By: Relevance
“…The recent discovery of miRNAs in CSCs has broadened the area of gene regulation implicated in tumorigenesis and CSC modulation (35,42,43). In this study, we observed that HA is capable of stimulating DOT1L and H3K79 methylation in CSCs.…”
Section: Discussionsupporting
confidence: 51%
“…The recent discovery of miRNAs in CSCs has broadened the area of gene regulation implicated in tumorigenesis and CSC modulation (35,42,43). In this study, we observed that HA is capable of stimulating DOT1L and H3K79 methylation in CSCs.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, the extent of sequence complementarity between the 5′-seed region of the loaded miRNA with that of its target mRNA 3′UTR largely dictates whether individual mRNAs are inactivated via cleavage, translational repression, or deadenylation (Figure 1; [13]). As will be discussed below, recent studies clearly demonstrate the importance of oncogenic signaling systems to impinge upon multiple steps of the miRNA biogenesis pathway, resulting in the aberrant expression and activity of miRNAs during tumorigenesis [1819]. …”
Section: Mirna Biogenesismentioning
confidence: 99%
“…Research has indicated that some miRNAs may function as oncogenes when up-regulated in HCC; to the contrary, the down-regulated miRNAs suggested them as tumor suppressors [7, 8]. Functioning as tumor suppressors, let-7 miRNAs were found to repress Ras, Bcl-xl, MAPK, c-Myc, cyclin D1 and other oncogenes in HCC [8, 9].…”
Section: Introductionmentioning
confidence: 99%